An examination of some proposed correlates of depressive illness - Krenz, Rosemarie Grace Selma (Department of Psychology, 2015)
Ten depressed subjects, ten recovered subjects and ten control subjects were assessed by the use of the Beck Depression Inventory, the Hostility Direction of Hostility Questionnaire, the Rotter Internal-External Control Scale and the Bene Anthony Family Relations Test. The depressed subjects differed significantly from the recovered and control group in the amount of hostility shown, and from the control group in the direction of hostility. Depressives did not differ significantly from the other two groups in their scores of the amount of internal control, nor in the way they perceived family relations in childhood. The results were seen to support Freud's and Bibring's theories concerning amount and direction of hostility. Rotter's internal-external control hypothesis could not be demonstrated. Nor did family feelings in childhood contribute to Bibring's theory of helplessness. The Family Relations Test was not able to distinguish between family relations of depressives and non- depressives.